2019
DOI: 10.1109/jphotov.2019.2929418
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an RbF Post Deposition Treatment of CIGS Solar Cells in Dependence on the Cu Content of the Absorber Layer

Abstract: In this contribution, the effectiveness of an RbF post deposition treatment (PDT) is evaluated in dependence on the Cu content of the absorber layer of Cu(In,Ga)Se 2 solar cells. It is shown that the PDT only acts beneficially on the open-circuit voltage and fill factor (FF) on samples with rather high Cu content, while it deteriorates all parameters of the solar cells in samples with low Cu content. In order to clarify the behavior of the open-circuit voltage, the well-known exchange mechanism of Rb and Na du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 26 publications
8
61
0
Order By: Relevance
“…For small bandgap CIGSe cells with NaF and KF‐PDT, a rollover of the JV curve at low temperatures was observed, which was explained by a barrier at the Mo/CIGSe interface 26 . Kodalle et al have also reported a barrier for the photocurrent for RbF‐treated CIGSe cells 27 . But our alkali‐treated samples exhibit a different behavior; the light JV curves show a double diode behavior, that is, a clear resumption of the injection current upon higher voltage, and not any saturation of the current density, which is a behavior that has not been reported for KF‐treated CIGSe cells.…”
Section: Resultsmentioning
confidence: 98%
“…For small bandgap CIGSe cells with NaF and KF‐PDT, a rollover of the JV curve at low temperatures was observed, which was explained by a barrier at the Mo/CIGSe interface 26 . Kodalle et al have also reported a barrier for the photocurrent for RbF‐treated CIGSe cells 27 . But our alkali‐treated samples exhibit a different behavior; the light JV curves show a double diode behavior, that is, a clear resumption of the injection current upon higher voltage, and not any saturation of the current density, which is a behavior that has not been reported for KF‐treated CIGSe cells.…”
Section: Resultsmentioning
confidence: 98%
“…This result is consistent with other studies. 58,59 This is expected to be due to the occupation of the CIGS/Mo interface with heavier alkali metals 8 …”
Section: Resultsmentioning
confidence: 99%
“…[22,30] Losses in open-circuit voltage (V oc ) are not often observed and are attributed to the absence of an ordered defect compound (ODC) at the CIGS surface or a too low Cu/ (InþGa) ratio. [31,32] In this contribution, we apply alkali treatments on AlO x backpassivated solar cells and find that this combination deteriorates the solar cell performance. An injection barrier at room temperature and losses in V oc are observed.…”
Section: Introductionmentioning
confidence: 99%